2013
DOI: 10.1038/nmat3521
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrastable glasses from in silico vapour deposition

Abstract: Glasses are generally prepared by cooling from the liquid phase, and their properties depend on their thermal history. Recent experiments indicate that glasses prepared by vapour deposition onto a substrate can exhibit remarkable stability, and might correspond to equilibrium states that could hitherto be reached only by glasses aged for thousands of years. Here we create ultrastable glasses by means of a computer-simulation process that mimics physical vapour deposition. These stable glasses have, far below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
220
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(252 citation statements)
references
References 33 publications
22
220
2
1
Order By: Relevance
“…The studies that have most carefully examined this regime have thus relied on alternative preparation schemes. In simulations, non-local Monte Carlo sampling has been used to achieve equilibration at densities otherwise unreachable (82,73); in experiments, vapor deposition has been used to generate ultrastable glasses (83). Although the details vary, the key result is that both schemes give access to equilibrium glasses for which τα τexp τ β .…”
Section: Gardner Transition and Marginal Glass In Finite Dimensionsmentioning
confidence: 99%
“…The studies that have most carefully examined this regime have thus relied on alternative preparation schemes. In simulations, non-local Monte Carlo sampling has been used to achieve equilibration at densities otherwise unreachable (82,73); in experiments, vapor deposition has been used to generate ultrastable glasses (83). Although the details vary, the key result is that both schemes give access to equilibrium glasses for which τα τexp τ β .…”
Section: Gardner Transition and Marginal Glass In Finite Dimensionsmentioning
confidence: 99%
“…This includes the Adam-Gibbs derivation of the structural relaxation [7,8] built on the thermodynamic notion of the configurational entropy [9] -, the mode-coupling theory [10] and extensions [11], the random first-order transition theory (RFOT) [12], the frustrationbased approach [13], as well as the so-called elastic models [14,15]. The search of a link between structural ordering and slow dynamics motivated several studies in liquids [16][17][18][19], colloids [20][21][22] and polymeric systems [20,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the boson peak frequency and low-frequency quasilocalization affects the stability of glasses subject to excitations [23][24][25]: the glass is more stable with higher boson peak frequency and weaker quasilocalization [larger p(ω)]. Figure 2 indicates that both pinning protocols stabilize the glass by increasing the boson peak frequency.…”
mentioning
confidence: 99%